The low-bias conducting mechanism of single-molecule junctions constructed with methylsulfide linker groups and gold electrodes - Wang, Minglang; Wang, Yongfeng; Sanvito, Stefano; Hou, Shimin (The Journal of chemical physics, 2017)
The atomic structure and electronic transport properties of two types of molecular junctions, in which a series of saturated and conjugated molecules are symmetrically connected to gold electrodes through methylsulfide groups, are investigated using the non-equilibrium Green’s function formalism combined with density functional theory. Our calculations show that the low-bias junction conductance is determined by the electronic tunneling between the two Au–S donor-acceptor bonds formed at the molecule-electrode interfaces. For alkanes with 4, 6, and 8 carbon atoms in the chain, the Au–S bonds moderately couple with the σ-type frontier molecular orbitals of the alkane backbone and thus prefer to be coplanar with the alkane backbone in the junction. This results in an exponential decrease of the junction conductance as a function of the number of methylene groups. In contrast, the Au–S bonds couple strongly with the π-type orbitals of the 1,4’-bis(methylsulfide)benzene and 4,4’-bis(methylsulfide)biphenyl molecules and thus tend to be perpendicular to the neighboring benzene rings, leading to the rather large junction conductance. Our findings contribute to the understanding of the low-bias conducting mechanism and facilitate the design of molecular electronic devices with methylsulfide groups and gold electrodes.